Bullshit jobs and universal basic income - Dragoš, Srečo (Anthropological notebooks, 2021)
David Graeber devotes the last section of the last chapter of his last book to Universal Basic Income (UBI). In freeing human labour from its market form (decommodification), Graeber is thinking in particular of bullshit jobs, the central feature of which is the meaninglessness and uselessness of the tasks, since they contribute neither to social nor individual well-being. Because Graeber did not elaborate on this idea of the feasibility of UBI, it is helpful to consider some critical objections in this regard; for example, is the proposed UBI too anti-capitalist and, in this sense, utopian? Moreover, if UBI did reduce the amount of junk and bullshit jobs, wouldn’t it simultaneously erode the labour market and the foundations of the work ethic? Finally, wouldn’t the introduction of UBI represent an excessive burden on public finances, without the support of which UBI is unfeasible? In this paper, I prove that the answer to these questions is: definitely not. This means that Graeber is right—especially in relation to the empirical data that are typical of Slovenia.
Keywords: bullshit jobs; decommodification; dekomodifikacija; Graeber, David; junk jobs; nesmiselno delo; ničvredno delo; socialna država; universal basic income; univerzalni osnovni dohodek; welfare state